Analisis Penerapan Aplikasi Mobile banking pada Nasabah Bank Sulteng Cabang Sigi - Yunita Angelika; Sugianto Sugianto; Abdul Pattawe; Ilham Pakkawaru (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The low level of mobile banking adoption at PT. Bank Sulteng Sigi Branch as a representative of regional banks in rural areas is the background of this study. This study aims to analyze the adoption of mobile banking applications and identify the factors that influence it, namely ease of use, perceived benefits, security, digital literacy, and technological infrastructure. A quantitative approach with a survey method was used through the distribution of a five-point Likert scale questionnaire to 85 customers, and analyzed using validity tests, reliability, classical assumption tests, and multiple linear regression assisted by SPSS. The results of the study indicate that all five variables simultaneously have a significant effect, while partially only perceived benefits, digital literacy, and technological infrastructure have a positive and significant effect. In conclusion, these three factors are the main drivers of mobile banking adoption at regional banks in rural areas, so it is expected to be a consideration for Bank Sulteng in designing strategies to improve mobile banking adoption that are appropriate to the characteristics of customers in the Sigi area.